Inside Cover: Targeted Delivery of Proteasome Inhibitors to Somatostatin‐Receptor‐Expressing Cancer Cells by Octreotide Conjugation (ChemMedChem 12/2015). Issue 12 (December 2015) - Beck, Philipp; Cui, Haissi; Hegemann, Julian D.; Marahiel, Mohammed A.; Krüger, Achim; Groll, Michael
Abstract : The inside cover picture shows the first small‐molecule proteasome inhibitor (PI) conjugate for targeted delivery. These were created by fusing PIs to a synthetic ligand of somatostatin receptors, which are highly expressed in a variety of tumors. Clinical applications of PIs are so far limited to peripheral blood cancers due to the pronounced cytotoxicity towards all cell types. Thus, targeted delivery of PIs could permit treatment of other cancers along with decreasing side effects. The cytotoxicity of this conjugate against cells with high levels of somatostatin receptors was increased up to 11‐fold in comparison with a nontargeting surrogate. More details can be found in the Communication by Philipp Beck, Haissi Cui, Michael Groll et al. onpage 1969 in Issue 12, 2015 (DOI:10.1002/cmdc.201500449 ).